Konflik Sosial dalam Pembangunan Infrastruktur SDA Kasus Waduk Jatigede - Setianto, Suryawan (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2014)
Infrastructure development in Indonesia is still frequently exposed to the problems of social conflict, not least in the construction of reservoirs. In the past 10 years, there has been 515 cases of conflict in the infrastructure sector. Potential conflicts can occur in any stage of development are listed in Survey, Investigation, Land Acquisition, Construction, Operation and Maintenance (SIDLACOM). This study aims to analyze the conflict in Jatigede Reservoir construction, with hope that can be used as a reference in the future to minimize the conflict. This research using qualitative approach. Data were collected through observation, interviews, and literature studies. Respondents are stakeholders that involved in Jatigede Dam development, community leaders and non governmental organization leader. Analysis using the map conflict, conflict dynamics and the sequence of events that important. This study shows that there are some important events underlying the emergence of social conflict. Stakeholders involved in the development of Jatigede Reservoir has a diverse relationship,ranging from alliance to non violent conflict. The dynamics of the conflict escalated and decrease in a particular period.